High level expression of nicotinamide nucleoside kinase from Saccharomyces cerevisiae and its purification and immobilization by one-step method - He, Jian-Ju; Liu, Xin-Xin; Li, Ying; Wang, Zhe; Shi, Hong-Ling; Kan, Yun-Chao; Yao, Lun-Guang; Tang, Cun-Duo (Frontiers in Bioengineering and Biotechnology, 2023)
Nicotinamide riboside kinase1 (NRK) plays an important role in the synthesis of β -nicotinamide nucleotide (NMN). NMN is a key intermediate of NAD+ synthesis, and it actually contribute to the well-being of our health. In this study, ScNRK1 was cloned from Saccharomyces cerevisiae and successfully expressed. After determination and conversion, the enzyme activity in the fermentation broth was 14.75 IU/mL, and the specific enzyme activity after purification was 2252.59 IU/mg. Using the metal affinity tag immobilization technique, the optimum temperature of the immobilized enzyme was increased by 10°C compared with the free enzyme, and the temperature stability was improved with little change in pH. Moreover, the activity of the immobilized enzyme remained above 80% after four cycles of immobilized reScNRK1, which makes the enzyme more advantageous in the enzymatic synthesis of NMN.